2000
DOI: 10.2307/2672914
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Disclosure Practices, Institutional Investors, and Stock Return Volatility

Abstract: This paper investigates whether the quality of a firm's disclosure practices affects the composition of a firm's institutional investor base and whether this association has implications for a firm's stock return volatility. The findings indicate that firms with higher disclosure quality, as measured by AIMR rankings, have greater institutional ownership, but the particular types of institutional investors that are attracted to disclosure quality tend to have no net impact on firms' stock return volatility. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
692
8
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,262 publications
(781 citation statements)
references
References 15 publications
(35 reference statements)
41
692
8
6
Order By: Relevance
“…In addition, Bushee and Noe (2000) found that institutional investors are more attracted by more informative firms. In our study, we explore the converse association.…”
Section: Literature Review and Research Questionsmentioning
confidence: 98%
“…In addition, Bushee and Noe (2000) found that institutional investors are more attracted by more informative firms. In our study, we explore the converse association.…”
Section: Literature Review and Research Questionsmentioning
confidence: 98%
“…Bushee & Noe [3] conclude that in the US market, better disclosure gives good signal to the market, removing the uncertainty caused by the non-liberation of information. Consequently, it results in a reduction of prices volatility.…”
Section: Previous Literature and Hypotheses Developmentmentioning
confidence: 99%
“…If companies convey information to the market frequently, the impact of new information about its performance will decrease, causing a lower variation on prices. As disclosure increases, the company's risk decreases, causing a smooth in the stock price volatility [3,[16][17][18].…”
Section: Previous Literature and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The AICPA's special committee on financial reporting (American Institute of Certified Public Accountants (AICPA), 1994) found that the benefit of greater disclosure is a lower cost of equity. Bushee and Noe (2000) focused on the cross-sectional relationship between risk and disclosure. Several of the relevant theories related to risk disclosure are also stated below: …”
Section: Background and Related Literaturementioning
confidence: 99%